IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH DALAM UPAYA MENINGKATKAN MUTU PENDIDIKAN DI MTs AL-FALAHIYAH PURASEDA - Nur Amelliany Rosadi; Rahmawati Alwi; Fuad Ahmad Riva’i (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2024)
School based management is a strategy and model that aims to improve the quality of education. The importance of this research is to find out school based management, quality of education, and implementation of school-based management in an effort to improve the quality of education at Junior High School Al-Falahiyah Puraseda. This research was conducted at Junior High School Al-Falahiyah Puraseda. It is a phenomenological research using a naturalistic qualitative approach. Data collection techniques used are interviews, observation, and documentation. The data analysis technique used is Miles and Huberman's. This study uses two data validity tests, a dependability test. The results of this study indicate that The SBM that has been implemented has gone well starting from the creation of the vision, mission and objectives of the school, the structural creation of teaching staff and students, the creation of educational activity committees, the involvement of all educational elements who participate and work together, to the evaluation. The condition of the quality of education meets educational standards, marked by the existence of a best input, process, outpute, and outcome. Through the implementation of SBM the quality of education has increased.